Analisis Peningkatan Kemampuan Public Speaking Dari Menonton K-Drama Bagi Siswi SMA Negeri No 09 Palembang - Windy; Achmad Syarifudin; Manalullaili (CV. ITTC INDONESIA, 2023)
Korean culture called Hallyu has produced many products such as movies, music, food, drama series, fashion and lifestyle. These Hallyu products spread all over the world with thedevelopment of science and technology. Therefore, through research, researchers have problems with the type of Korean language that can be used as a style of speaking in public when watching Korean dramas according to the scriptwriter's direction and inclination. This research is entitled